A new species of Cylindrostethus Mayr (Hemiptera, Gerromorpha, Gerridae) for the Neotropical Region, with an identification key for the species of Group 1 sensu Drake 1952 - Floriano, Carla Fernanda Burguez; Cavichioli, Rodney Ramiro (Zootaxa, 2013)
A new species of Cylindrostethus Mayr, C. meloi sp. nov. is described and illustrated from the state of Amazonas, Brazil. This species can be easily distinguished from congeners by the shape of the proctiger. An identification key for the species of Group 1 sensu Drake 1952 is presented.